2014
DOI: 10.1016/j.ijmm.2014.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia psittaci: New insights into genomic diversity, clinical pathology, host–pathogen interaction and anti-bacterial immunity

Abstract: The distinctive and unique features of the avian and mammalian zoonotic pathogen Chlamydia (C.) psittaci include the fulminant course of clinical disease, the remarkably wide host range and the high proportion of latent infections that are not leading to overt disease. Current knowledge on associated diseases is rather poor, even in comparison to other chlamydial agents. In the present paper, we explain and summarize the major findings of a national research network that focused on the elucidation of host-path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 107 publications
3
80
0
1
Order By: Relevance
“…The clinical history, signology, necropsy findings, and histologic lesions of all tested birds were compatible with those described previously for psittacine birds infected by C. psittaci (15,16,29,32). In this case, the presence of the bacteria was initially demonstrated through a 16S rRNA gene sequence analysis using specimens obtained from the liver of affected birds; together with the immunofluorescence results on the same hepatic tissue, these analyses confirmed the diagnosis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The clinical history, signology, necropsy findings, and histologic lesions of all tested birds were compatible with those described previously for psittacine birds infected by C. psittaci (15,16,29,32). In this case, the presence of the bacteria was initially demonstrated through a 16S rRNA gene sequence analysis using specimens obtained from the liver of affected birds; together with the immunofluorescence results on the same hepatic tissue, these analyses confirmed the diagnosis.…”
Section: Discussionsupporting
confidence: 86%
“…It has been demonstrated that birds may remain carriers during latent infections, which can be reactivated if the birds are subjected to stressful conditions, such as those that occur during captivity (e.g., overcrowding, transportation, malnutrition, temperature changes, and manipulation). Therefore, when a latently infected bird restarts bacterial excretion, it becomes an infection source for other birds and humans (11,12,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine if the observed effect is specific for infection with C. burnetii, we exemplarily compared the temporal response pattern of IL-12 transcription in bovine MDM cultures to that in E. coli LPS and another intracellular pathogen, C. psittaci. C. psittaci has a broad host range, including cattle (61), and replicated efficiently in the bovine MDM cultures (K. Hillarius and A. Berndt, data not shown). Contrary to NMI infection, both treatments induced increasing IL-12 expression during the first 24 h, implying that C. burnetii specifically controls the host response in bovine macrophages to allow replication without significant inflammatory cytokine production.…”
Section: Discussionmentioning
confidence: 97%
“…Depending on the species and age of the bird and the virulence of the infectious bacterial strain, avian chlamydiosis can be subclinical or characterised by respiratory, digestive, or systemic disorders (Knittler and others 2014). …”
mentioning
confidence: 99%